- #1
Vi Nguyen
- 13
- 0
Rewrite in logarithmic form:
e^(-1) = c
e^(-1) = c
The logarithmic form of e^(-1) = c is ln(c) = -1.
To solve for c, take the natural logarithm of both sides: ln(e^(-1)) = ln(c). This simplifies to ln(c) = -1. Then, use the inverse property of logarithms to rewrite the equation as c = e^(-1).
The value of c represents the result of raising e to the power of -1, which is approximately 0.3679.
Yes, the exponential form of e^(-1) = c is c = e^(-1).
The number e, also known as Euler's number, is a mathematical constant that is approximately equal to 2.71828. It is commonly used in logarithmic and exponential functions, and in this equation, it represents the base of the natural logarithm.